2021
DOI: 10.5114/aoms/142350
|View full text |Cite
|
Sign up to set email alerts
|

Calendula officinalis green-mediated silver nanoparticles: Formulation, characterization and assessment of colorectal cancer activities green-mediated silver nanoparticles.

Abstract: IntroductionThe biosynthesis of metal nanoparticles using medicinal plants is not only economical but also environmentally friendly as well as having miscellaneous biomedical applications. In the present study, silver nanoparticles were green-synthesized using the aqueous extract of Calendula officinalis.Material and methodsThe synthesized AgNPs@Calendula officinalis were characterized by analytical techniques including EDX, FE-SEM, XRD, UV-Vis., and FT-IR. The anti-human colorectal cancer activities of AgNPs@… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Silver nanoparticles were previously obtained by different groups of researchers using extracts from C. officinalis plants. Silver nanoparticles are usually obtained by reacting plant extracts with silver nitrate solution (El-Kemary et al, 2016;Xu et al, 2021;Asif et al, 2022;Liaqat et al, 2022). However, it was shown that such NPs can also be obtained using a solution of silver sulfate (Olfati et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Silver nanoparticles were previously obtained by different groups of researchers using extracts from C. officinalis plants. Silver nanoparticles are usually obtained by reacting plant extracts with silver nitrate solution (El-Kemary et al, 2016;Xu et al, 2021;Asif et al, 2022;Liaqat et al, 2022). However, it was shown that such NPs can also be obtained using a solution of silver sulfate (Olfati et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…However, it was shown that such NPs can also be obtained using a solution of silver sulfate (Olfati et al, 2021). Dried leaves or flowers (El-Kemary et al, 2016;Olfati et al, 2021;Xu et al, 2021;Balciunaitiene et al, 2022) were used for this purpose. At the same time, until now, the hairy roots of these plants have not been used to obtain silver nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…115 The anti-colorectal cancer activity of silver nano-particles of C.officinalis was evaluated against MTT assays which decreased the colorectal cell lines. 4 The cytotoxic activity of some isolated compounds like lutein, lupeol, and eugenols were evaluated by MTT assays against breast cancer cell lines (MCF-7 and MDA-MB-231) and normal breast cell line (MCF 10A). The messenger ribonucleic acid (mRNA) expression level of p53, caspase-3, and bax genes were measured which were found to increase in both cancer cells, and B-cell lymphoma 2 (Bcl-2) gene expression deduced in treated breast cancer cells.…”
Section: Anticancer Activitymentioning
confidence: 99%
“…[1][2][3] The name calendula comes from the Latin word "calendas," which means "first of the month." 4 The term marigold comes from calendula, which was formerly known as "gold's" and was connected to Queen Mary and the Virgin Mary. 5 C. officinalis is sessile, hispid, acute, oblanceolate, annual, or biennial herbaceous plant that is between 30 and 60 centimeters height.…”
Section: Introductionmentioning
confidence: 99%